Evaluation of CellerateRX Surgical Powder utility in reducing groin complications after femoral exposure - Vy C. Dang, BS; Eric K. Peden, MD; Trisha Roy, MD, PhD; Alan B. Lumsden, MD; Linda Le, MD; Charudatta S. Bavare, MD; Sohaib K. Mhaidi, MD; Maham Rahimi, MD, PhD (JVS-Vascular Insights)
Objective: Vascular procedures involving groin incisions for femoral exposure often have complications that delay wound healing. These complications include but are not limited to the development of seromas, hematomas, skin necrosis, or infection requiring reintervention leading to readmission, increased length of stay, and increased morbidity and mortality, including limb loss. In this non-concurrent cohort study, we evaluate the usefulness of CellerateRX Surgical Powder in preventing postoperative groin complications. We compare the outcomes of groin incisions that received standard surgical wound care and those in which CellerateRX Surgical Powder was applied to the surgical incision prior to primary closure. Methods: Groin incisions required for femoral exposure in vascular surgery procedures were considered. The control group included cases between 2020 and 2021. Exclusion criteria included patients <18 years of age, those with a bovine allergy, those with an active groin infection, and those undergoing a repeat femoral exposure. Bilateral groin incisions were counted as two separate constituents in the overall sample. The perioperative protocol in the management of these patients included 1-hour preoperative vancomycin (15 mg/kg intravenously [IV])/ceftriaxone (2 g IV), double skin preparation with 4% chlorhexidine, hair removal with surgical clippers, Ioban, postoperative doxycycline (100 mg oral or IV twice daily for 24 hours), and negative pressure wound therapy or a muscle flap in high-risk patients. Patients between 2022 and 2023 who met the described inclusion criteria were enrolled into the experimental group. The only change to the perioperative protocol of the experimental group was the addition of CellerateRX Surgical Powder to the surgical wound before closure. Patients were followed for 6 months. The primary outcome was the number of groin complications that required return to the operating room (eg, seroma, hematoma, and infection). Results: The control group consisted of 136 groins, 17 (13%) of which developed complications—7 (5.1%) seromas, 2 (1.5%) hematomas, 5 (3.7%) soft tissue infections, and 3 (2.2%) skin necrosis cases. The treatment group consisted of 20 groins, 3 (15%) of which developed complications—two seromas and one soft tissue infection. A two-tailed Fisher's exact test demonstrated no statistically significant association between the presence of complications and the treatment group (P = .49, α = 0.05); however, patients in the experimental cohort were found to be a higher risk group, having significantly higher prevalence of diabetes and surgeries using a prosthetic. Conclusions: Based on the results of this study, we cannot conclude that a packing application of CellerateRX Surgical Powder alters the risk of developing postoperative groin complications compared with standard wound care. No hematomas and skin necrosis were observed in the treatment group; however, confirmation of the benefit should be confirmed in larger, cohort-controlled studies.